1980
DOI: 10.1111/j.1744-6570.1980.tb02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐appraisal of Job Performance

Abstract: MY interest in self-appraisal has focused primarily on self-ratings of present job performance. I have been especially interested in how selfappraisals affect the respective individuals' reactions to a feedback interview with a supervisor who has also rated their performance in a formal performance appraisal program. I first became interested in self-appraisals of job performance in connection with an intensive research study of the appraisal interview conducted in the General Electric Company (Meyer, Kay, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 5 publications
(3 reference statements)
3
61
1
Order By: Relevance
“…However, this doesn't mean that people want to be compared with others by third parties. It is also true that people generally think they are above average (Meyer, 1980), so most feel they will benefit from these ratings and comparison. Although employees may say they want to be rated, their actions suggest otherwise.…”
Section: Feedback Is Not Accepted or Acted Onmentioning
confidence: 99%
“…However, this doesn't mean that people want to be compared with others by third parties. It is also true that people generally think they are above average (Meyer, 1980), so most feel they will benefit from these ratings and comparison. Although employees may say they want to be rated, their actions suggest otherwise.…”
Section: Feedback Is Not Accepted or Acted Onmentioning
confidence: 99%
“…Shay and Baack (2004) note that self-assessment of performance could bring in a variety of sources of bias such as leniency error (Meyer 1980), restriction of range (Thornton 1980), and halo error (Holzbach 1978). This study can be distinguished from other expatriate studies since it makes use of a sample of expatriates in which virtually all participants had moved from a subsidiary location to the corporate headquarters.…”
Section: Limitationsmentioning
confidence: 99%
“…Many previous studies rely on self-reported effectiveness ratings as the source of outcome data [15,38] which introduce a number of problems, including leniency error [39], restriction of range [40], and halo error [41]. Some other studies have utilized performance data gathered from supervisors [42], which may have concerns on the rater's opportunity for regular and frequent observations of the expatriate's on-the-job behaviors.…”
Section: B Data Collectionmentioning
confidence: 99%